Analysis of national health accounts in Iran (2002–2020) - Abdoreza Mousavi; Mahdi Mokhtari-Payam; Aliakbar Fazaeli; Mohammad Bakhtiari Aliabad (Payesh)
Objective (s): Comprehensive data on health expenditures is crucial not only for effective policymaking but also for achieving universal health coverage and health-related sustainable development goals. This study provides a detailed analysis of Iran's national health accounts from 2002 to 2020, offering insights into trends and patterns in healthcare spending during this period. Methods: This descriptive study utilizes data from Iran’s national health accounts to examine health expenditures across various dimensions, including health functions, healthcare service providers, financing agents, and funding sources, covering the period from 2002 to 2020. Descriptive statistics were employed to analyze the data. Results: Total health expenditures experienced a substantial rise, increasing from 53,351 billion Rials in 2002 to 2,372,718 billion Rials in 2020, giving a 44.5-fold increase. However, when adjusted for constant values, the results decreased to a 2.7-fold increase. During the period from 2002 to 2020, curative care accounted for the largest share of expenditures at 57.3%, followed by pharmaceuticals and other medical goods dispensed to outpatients at 17.1%. The majority of health expenditures were allocated to hospital providers, ambulatory care providers, and pharmacies, along with other retailers of medical goods, representing 39.6%, 30.2%, and 16.4%, respectively. The share of out-of-pocket (OOP) payments decreased from 50.6% to 35%. Furthermore, 30% of expenditures were financed by the public sector, while the private sector covered the remaining 70%. Conclusion: In Iran's healthcare system, a substantial proportion of expenditures is allocated to curative care, with hospitals serving as the primary recipients of these funds. Moreover, a significant share of healthcare expenses is financed through OOP payments, which increases the risk of catastrophic health expenditures for households. Consequently, it is essential to reduce these payments by expanding insurance coverage and enhancing the existing prepayment methods. Furthermore, prioritizing sustainable financing and enhancing financial resources within the health system is crucial for ensuring equitable access to healthcare services.